BEARING CAPACITY OF CONE SHAPED FOUNDATIONS WITH SEMI ANGLE β VARIATION AND DIFFERENT ROUGHNESS - Moningka, George; Sompie, Oktovian B. A.; Sumampouw, J. A. R. (Sam Ratulangi University, 2013)
A properly designed foundation throughout the soil without overstressing the soil. Overstressing the soil can result in either excessive settlement or shear failure of the soil, both on which cause damage to the structure; thus, geotechnical and structural engineers who design foundations must evaluate the bearing capacity of soils. Depending on the structure and soil encountered, various types of foundation are used. The problem of bearing capacity of cone shaped foundation with semi angle β variation; 15°, 30°, 45°, 60°, 90° and different roughness; perfectly smooth and perfectly rough, in homogeneous soil and subjected to axial load, is analyzed on the basis of plastic theory. The soil is considered as a perfectly rigid plastic material obeying the MOHR-COULOMB failure criterion. An experimental investigation was made to obtain penetration resistance for estimating the ultimate bearing capacity of cone foundation with various semi angle β and different roughness in sands (c = 0) and clays (ɸ = 0). The Mangatasik Dry Sand and Wenwin Soft Clay were used in this tests. The experimental values were found to agree well with theoretical bearing capacity of cone shaped foundations.Keywords : bearing capacity, cone shaped foundation, semi angle β, roughness, sand, clay.